1995
DOI: 10.1111/j.1151-2916.1995.tb08622.x
|View full text |Cite
|
Sign up to set email alerts
|

Incommensurately Modulated Polar Structures in Antiferroelectric Sn‐Modified Lead Zirconate Titanate: The Modulated Structure and Its Influences on Electrically Induced Polarizations and Strains

Abstract: Zrn.,,Snn.,S),.,sTi,lo, (PZST 45/y/2), have been studied by hot-stage transmission electron microscopy (TEM), dielectric spectroscopy, Sawyer-Tower polarization (P-E) measurements, and electrically induced strain (E-E) techniques. The compositional range chosen for investigation was 0 < y < 0.09. Electron diffraction confirmed the existence of $( 110) superlattice reflections in the previously designated antiferroelectric tetragonal state. For PZST 451012, the room-temperature modulated structure was found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
102
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(105 citation statements)
references
References 14 publications
3
102
0
Order By: Relevance
“…The structural origin for these superlattice reflections is still under debate. 2,[5][6][7]9,21 However, the present in situ TEM study provides valuable insight into the physics mechanism for the presence of these superlattice reflections. It is clear in Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The structural origin for these superlattice reflections is still under debate. 2,[5][6][7]9,21 However, the present in situ TEM study provides valuable insight into the physics mechanism for the presence of these superlattice reflections. It is clear in Fig.…”
mentioning
confidence: 99%
“…These results are consistent with previous observations from other researchers. [5][6][7] In order to determine the field level needed for the in situ TEM study and to assess the sample geometry effect on the field-induced antiferroelectric-to-ferroelectric phase transformation, a dimpled and annealed 3-mm-diam disk specimen was tested for the hysteresis measurement and the result is also plotted in Fig. 3.…”
mentioning
confidence: 99%
“…Figure 4(b) displays the changes of the characteristic antiferroelectric {21 3 4 } superlattice peak. In the virgin state with the mixed antiferroelectric and ferroelectric phases, this peak is clearly seen.…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7][8] Most studied antiferroelectric ceramics in literature are based on the prototype compound PbZrO 3 with a perovskite structure, in which the phase transition manifests itself in the development of a large polarization and is generally accompanied by a significant volume expansion when the applied field exceeds a critical magnitude E F . [2][3][4][5][6][7][8][9][10] The associated volume change at the phase transition has been explored as a mechanism for toughening the ceramic. 11 Recently, it has been reported that some chemically modified PbZrO 3 -based ceramics can exist either in the antiferroelectric or ferroelectric state at room temperature, depending on their thermal history.…”
mentioning
confidence: 99%
See 1 more Smart Citation